Mewujudkan Desa Tertata Dan Produktif: Peran Mahasiswa Dalam Administrasi Dan Pemberdayaan Masyarakat - Isa Kholili; Wahyu Sulaiman; Rifqi Huda; Ulin Nuha; Zulfatun Naimah (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2026)
This Community Service Program (KP2M) was conducted in Ketawang Village, Malang Regency, with the primary goal of resolving issues related to service administration and the empowerment of women's groups. Ketawang Village needed more efficient governance improvement and an enhanced role for the PKK women in economic activities. The program focused on two core activities: (1) Assistance in Organizing Village Service Administration and (2) Socialization, Planning, and Empowerment of the PKK Women's Group. The methodology involved intensive mentoring and focused training. Administrative activities included archives organization and data digitalization to improve service speed and transparency. Meanwhile, PKK activities involved program planning training and initiating micro-enterprise development to increase family income. Results showed a significant improvement in the efficiency of village services and the emergence of more structured work programs from the PKK group. This intervention successfully laid the foundation for Ketawang Village to become a more organized, transparent, and productive village by boosting the capacity of village officials and the PKK women.